Correlation Between Compressive Strength and Tensile Strength/ Index Strength of Some Rocks of North-West Frontier Province (Limestone and Granite) - Din, Feroz; Rafiq, Mohammad (Journal of Himalayan Earth Sciences, 1997)
The use of the building Stones is increasing day by day and engineering activities are also in progress. Therefore, the mechanical properties of building stones such as limestones, marbles, granites etc. are required to be investigated to estimate the strength and give recommendations in designing safe structures. The present research deals with the investigation and correlation of compressive, tensile and index strength of granites and limestones from different localities of North-West Frontier Province. The test results are given in table 1-2, which reveal suitability of Shahbaz Garhi micro granite for heavy constructions and in foundations of buildings while Malakand granite in light constructions, crushed stones, floor material and ballast under railway tracks. The strength values of Cherat and Kohat limestones are low, and yew much suitable for cement, chemical industry and ballast under roads.